Hubungan Dukungan Keluarga dengan Keikutsertaan Wanita Usia Subur pada Program KB di Puskesmas Aramo Kecamatan Aramo Nias Selatan Tahun 2023 - Asweriawati Sarumaha; Adelina Sembiring; Lisbet Gurning; Sri Mulati Nendah (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
The high birth rate in Indonesia is one of the major problems and requires special attention in handling it. One form of special attention from the government in overcoming the high birth rate is implementing comprehensive family planning. The national family planning movement is prepared to build optimal human resources, characterized by increasing community participation in meeting the needs to be able to build prosperous families in the context of family planning services. The purpose of the study was to identify the relationship between family support and the participation of Women of Childbearing Age in the Family Planning Program at the Aramo Health Center, Aramo District, South Nias in 2023. The results of the cross-tabulation study showed a relationship between family support and the participation of women of childbearing age in the family planning program at the Aroma Health Center, South Nias in 2023 with a P value of 0.000 (P value <0.005), so Ho was rejected and Ha was accepted. Suggestions for midwifery services to provide education to increase family support with the participation of women of childbearing age.